Polylogical Core of Modern Intercultural Interaction Models - Astafyeva Olga Nikolaevna; Belyakova Irina Gennadievna (Randwick International of Social Science Journal, 2022)
The article is devoted to the problems of transformation and phenomenon of complication of intercultural communication models. The significance of the study lies in the fact that intercultural communication through the prism of cultural and civilizational developments reflects the sociocultural changes taking place at all levels of social development. The problem of application of theoretical knowledge about the communicative paradigm of modern culture with its polylogical core for the development of a specific model of intercultural communication and effective cultural policy relates to the difficulties of achieving compliance of the research results with the real state of the sociocultural environment. Basing on the previous and current research approaches and taking into consideration a systemic and synergistic approach as well as a dialogue concept, the authors aim to investigate theoretical modeling of intercultural interaction. As a result of investigation, the authors conclude that the study of models of intercultural interaction cannot be carried out without understanding the principles and factors of the dynamics of cultural changes in the modern world which allows us to consider the transition from a dialogue model to a polylogue model as a natural stage in the dynamics of culture. Also, the methodological set of philosophical and cultural studies of the dynamics of modern culture is proved as constantly expanding due to the new tendencies, like total digitalization. It is stated that overcoming outdated models of intercultural interaction and adopting the new ones is a long process that must be tested by the human society